1952
DOI: 10.1002/hlca.19520350102
|View full text |Cite
|
Sign up to set email alerts
|

Hans Rupe. 1866—1951

Abstract: wurde am 9. Oktober 1866 in Basel geboren, als Sohn des Kaufmanns Johannes Rupe und seiner Gattin MuthiZde, geb. Pischer, beide aus Westfalen stammend. Er durchlief in Basel die Primarschule und das nntere und obere Gymnasium. Schon als Knabe hatte er viel Anregung auf naturwissenschaftlichem Gebiet, zuniichst durch seinen Vater, der ursprunglich auch Chemie studiert hatte und als guter Pflanzenkenner mit den Kindern auf Wanderungen und wahrend der Ferienaufenthalte in den Alpen fleissig botanisierte. Besonder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1955
1955
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Rupe was appointed assistant professor in 1903. The institute was divided into two separate Chairs for Inorganic Chemistry and Organic Chemistry in 1912, which led to the appointment of Rupe as Director of Organic Chemistry, a position he held until his retirement in 1937 [1] [48].…”
Section: Institute Of Pharmacy Atmentioning
confidence: 99%
“…Rupe was appointed assistant professor in 1903. The institute was divided into two separate Chairs for Inorganic Chemistry and Organic Chemistry in 1912, which led to the appointment of Rupe as Director of Organic Chemistry, a position he held until his retirement in 1937 [1] [48].…”
Section: Institute Of Pharmacy Atmentioning
confidence: 99%
“…Kinetics. -In preceding kinetic investigations on rearrangements involving carboxamide-group migrations in the benzil-benzilic acid rearrangement we had found that for N,N-diphenyl-a$-dioxobutyramide [6] the rate of rearrangement is proportional to [OH-], but tends towards a plateau at high pH values; for quinisatine (6) no clear order of dependence of the rearrangement rate upon [OH-] had been found [7]. We have now measured the rate of rearrangement of l a -c at different alkali concentrations; on the same occasion, we have extended the range of our former measurements with 6, for which the course of the rearrangement had been established earlier [7].…”
Section: *-mentioning
confidence: 99%
“…For instance ester groups ROOC have been demonstrated to migrate in Wagner-Meerwein [3], pinacol [4] and benzil-benzilic acid rearrangements [ 5 ] . We have found two cases of migration of carboxamide groups in the benzil-benzilic acid rearrangement of an open-chain compound, Me-CO-CO-CONPh, [6], and of a cyclic amide, quinisatine (6) [7]. On the other hand, Kwart and coworkers [XI have shown that there is no shift of the carboxamide group in the alkali-catalyzed rearrangement of alloxane and its N-substituted derivatives but exclusively cleavage of the C-N bond and migration of the N-group; Smith and Kan [9] found the same result for the rearrangement of phthalonimide.…”
mentioning
confidence: 99%
“…Another problem which I found particularly intriguing was the remarkable acid-catalyzed rearrangement of α-cinenic acid 2 to geronic acid 3 , which I discovered by reading the obituary of Hans Rupe in Helvetica Chimica Acta. This transformation had been interpreted as requiring a long-range methyl group migration which, however, had no reasonable mechanistic rationale. What struck me immediately was the fact that this mysterious transformation might not involve a long-range methyl group migration at all: transfer of the carboxyl group to the carbon atom bearing the geminal methyl groups would also produce geronic acid!…”
mentioning
confidence: 99%